Through the Eyes of the Beholder: Simulated Eye-movement Experience (“SEE”) Modulates Valence Bias in Response to Emotional Ambiguity - Neta, Maital (Emotion, 2018)
Although some facial expressions provide clear information about people’s emotions and intentions (happy, angry), others (surprise) are ambiguous because they can signal both positive (e.g., surprise party) and negative outcomes (e.g., witnessing an accident). Without a clarifying context, surprise is interpreted as positive by some and negative by others, and this valence bias is stable across time. When compared to fearful expressions, which are consistently rated as negative, surprise and fear share similar morphological features (e.g., widened eyes) primarily in the upper part of the face. Recently, we demonstrated that the valence bias was associated with a specific pattern of eye movements (positive bias associated with faster fixation to the lower part of the face). In this follow-up, we identified two participants from our previous study who had the most positive and most negative valence bias. We used their eye movements to create a moving window such that new participants view faces through the eyes of one our previous participants (subjects saw only the areas of the face that were directly fixated by the original participants in the exact order they were fixated; i.e., Simulated Eye-movement Experience). The input provided by these windows modulated the valence ratings of surprise, but not fear faces. These findings suggest there are meaningful individual differences in how people process faces, and that these differences impact our emotional perceptions. Furthermore, this study is unique in its approach to examining individual differences in emotion by adapting a methodology previously used primarily in the vision/attention domain.